Recovery Compromised: Tracing the Structural Conditions that Perpetuate and Maintain Social Exclusion in Assertive Community Treatment - Horgan, Salinda; Krupa, Terry (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2012)
Concerns have been raised regarding the extent to which the services provided through the Assertive Community Treatment (ACT) model are based on an understanding of recovery as primarily a clinical phenomenon rather than a journey that is fundamentally about self-determination, social inclusion, citizenship and civil rights. Until recently, the limited degree of social inclusion experienced by users of ACT has been assumed to result from individual functioning or inadequate practitioner training. These explanations negate the role of organizing conditions in shaping a systematic approach to everyday practice that diminishes opportunities for inclusion. The current study identifies key areas where practices consistent with the current recovery vision and theories of social inclusion are superseded by accepted and legitimized forms of practice that are aligned with a medical model approach. The study explicates both how and why this happens in the course of everyday practice.